Long term survey of the butterfly fauna of Curitiba, Paraná, Brazil: How does a scientific collection gather local biodiversity information? (Lepidoptera: Papilionoidea) - J. H. Pérez; F. G. Gaviria-Ortiz; W. I. G. Santos; E. Carneiro; O. H. H. Mielke; M. M. Casagrande (SHILAP, 2017)
Butterfly species lists are commonly published aiming to describe local or regional diversity, thus being primordial tools for subsiding nature preservation and management. However, tropical lands usually lack this kind of information. Inventories of megadiverse organisms, such as butterflies, usually require long term studies to detect a substantial fraction of species present in certain location. Through biological collections in scientific institutions it is possible to preserve a considerate amount of biodiversity information, which is not available in the literature, but can promote studies over time. Aiming at supplementing the knowledge on butterfly diversity in Curitiba, Paraná, Brazil, and to demonstrate how a scientific collection accumulates such information from the nearby surroundings, this study lists all species of butterflies recorded in the city since 1938. Since then, 554 species were recorded. Although there have been large sampling efforts since the 60s, 45 species were only recorded in the last decade. Species lists published in 1938, 1995, 2011 and 2015 contributed to a considerable fraction of species records and monitoring, but species richness observed in each study is usually low (less than 1/3 of all historical records). Therefore, the long term deposition of specimens gathered in a single collection evidences that Curitiba harbors a distinct higher number of species, though new records are still frequent. Taking into account that long term surveys of megadiverse insects offer a more complete analysis of their biological diversity, studies measuring diversity impacts, such as urban sprawl, must include historical data whenever available.